Making Programming Accessible to Learners with Visual Impairments: A Literature Review - Hadwen-Bennett, Alex; Sentance, Sue; Morrison, Cecily (International Journal of Computer Science Education in Schools, 2018)
Programming can be challenging to learn and for visually impaired (VI) learners there are numerous additional barriers to the learning process. Many modern programming environments are inaccessible to VI learners, being difficult or impossible to interface with using a screen reader. A review of the literature has identified a number of strategies that have been employed in the quest to make learning to program accessible to VI learners. These can be broadly divided into the following categories; auditory and haptic feedback, making text-based languages (TBLs) accessible, making block-based languages (BBLs) accessible and physical artifacts. A common theme among the literature is the difficulty VI learners have in gaining an understanding of the overall structure of their code. Much of the research carried out in this space to date focuses on the evaluation of interventions aimed at VI high-school and undergraduate students, with limited attention given to the learning processes of VI learners. Additionally, the majority of the research deals with (TBLs), this is despite the fact that most introductory programming courses for primary learners use (BBLs). Therefore, further research is urgently needed to investigate potential strategies for introducing VI children in primary education to programming and the learning processes involved.